1993
DOI: 10.1139/g93-101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetics of the ribosomal (18S + 28S and 5S) DNA loci in primitive and advanced urodele amphibians

Abstract: In the present work we performed a cytogenetic analysis of the ribosomal (18S + 28S and 5S) loci in amphibian species belonging to the advanced family Salamandridae (genera Triturus, Salamandra, and Salamandrina) and in the primitive hynobiid Salamandrella keyserlingii (family Hynobiidae). In each analyzed karyotype the 5S rDNA sites appear to be stable, and definite in number, while an intraspecific variability both in number and chromosomal location of the 18S + 28S rDNA loci has been found in some Triturus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
48
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 24 publications
9
48
0
1
Order By: Relevance
“…Moreover, the loci have been mapped on different chromosomes in several fish species (Morán et al, 1996;Wasko et al, 2001), a condition often found in vertebrates (Lucchini et al, 1993;Suzuki et al, 1996). Our data show that in P. anhembi the 5S ribosomal site is syntenic with the 18S rDNA site, which is located subterminally on the short arm of the chromosome pair 21 (Fig.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Moreover, the loci have been mapped on different chromosomes in several fish species (Morán et al, 1996;Wasko et al, 2001), a condition often found in vertebrates (Lucchini et al, 1993;Suzuki et al, 1996). Our data show that in P. anhembi the 5S ribosomal site is syntenic with the 18S rDNA site, which is located subterminally on the short arm of the chromosome pair 21 (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Even the mapping of the 5S rDNA sites in fish has demonstrated that sites are frequently located at a single chromosome locus, which may correspond to an ancestral condition in this group (Martins & Galetti, 1999). In amphibians (Schmid et al, 1987;Lucchini et al, 1993) and fishes (Mazzei et al, 2004;Nirchio & Oliveira, 2006) the 5S rDNA genes can be located in one or more chromosomes. Variations in the 5S rDNA gene location may occur due to the presence of pseudogenes, insertions, deletions and repetitions, which have often been characterized in various organisms (Suzuki et al, 1996;Sadjak et al, 1998;Alves-Costa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in amphibians (Lucchini et al, 1993) and fishes (Martins and Galetti, 1999;, the 5S rDNA cistrons can be present in several chromosomes. Besides, the 45S and 5S rDNA loci may be syntenic (Morán et al, 1996) or located in distinct chromosome pairs (Martins and Galetti, 1999;Born and Bertollo, 2000), the last condition being commonly observed among fishes.The three Serrasalmus species showed a single 5S rDNA site, located on the same region of the medium-sized metacentric pair 7, coinciding with a C-positive heterochromatic band.…”
Section: Discussionmentioning
confidence: 99%
“…DOI: 10.1038/sj/hdy/6800070 to map repeated units of the two rDNA families (18S-28S rDNA and 5S rDNA) and to test the presence of (GATA) n and (TTAGGG) n repeats in the genome of this species. Available literature data report on the localization of major (18S-28S rDNA) and minor (5S rDNA) ribosomal clusters on different chromosome pairs as the most frequent configuration in vertebrates (see Lucchini et al, 1993;Suzuki et al, 1996). Since very little is known about rDNAs mapping in gastropods, we employed in addition to single colour FISH, simultaneous double-colour FISH to investigate about their physical relationship.…”
Section: Introductionmentioning
confidence: 99%